Routes of Delivery and Onset of Lactation - Jeerasap, Rungruedee; Phaiboonbunpot, Naunjun; Panikom, Somporn (Journal of Health Science of Thailand, 2017)
The onset of lactation (OL) is the maternal perception of milk coming-in by the feeling of breast fullness and prickly, dripping from the contra-lateral nipple when the baby nurses, milk running from the baby’s mouth and its gulping. Several studies found significant association of delivery routes and the onset of lactation yet without any evidence in Thai mothers. This prospective cohort study was to determine the onset of lactation time by maternal perception in 350 post-partum women who had delivered vaginally and by Cesarean section in Khon Kaen Hospital from April to May 2008. It was found that the mean time of the onset of lactation in vaginal and Cesarean delivery groups were 34.1, SD 18.3 and 44.2, SD 22.4 hours, respectively with statistical significance. The delayed onset of lactation (OL >72 hours) was 12 percent in the Cesarean section group and 3.4 percent in the vaginal group. (RR 3.58 CI 1.41-9.76) In conclusion, post- Cesarean mothers had significant longer OL time compared with vaginal mothers.